Detection of residual tumor cells in patients with malignant melanoma responding to immunotherapy - Brossart, Peter; Keilholz, Ulrich; Scheibenbogen, Carmen; Möhler, Thomas; Willhauck-Fleckenstein, Martina; Hunstein, Werner (Journal of immunotherapy, 1994)
Summary: - Recently, a highly sensitive assay combining reverse transcription and polymerase chain reaction (PCR) to assess for melanoma cells in peripheral blood has been developed. Detection of tyrosinase mRNA, a tissuespecific enzyme in melanocytes and melanoma cells, indicates the presence of melanoma cells in peripheral blood. We examined blood samples and bone marrow aspirates from 28 patients with metastatic malignant melanoma for presence of melanoma cells prior to and after therapy with interferon (IFN)-a and interleukin (IL)-2. Ten patients showed antitumor response to immunotherapy, including three complete (CR) and seven partial remissions (PR). Four patients (three PR, one stable disease) underwent subsequent resection of residual tumor lesions and had no clinical evidence of disease after surgery. Tyrosinase mRNA was detected in blood and bone marrow samples from all patients with malignant melanoma prior to and after immunotherapy, including those with no clinical evidence of disease (median disease—free survival 21 months, range 19-28 months). Tyrosinase transcripts were also detected in all patients with amelanotic melanoma. In contrast, no tyrosinase mRNA was detectable in any of 30 healthy persons or in six patients with other malignancies. The presence of residual melanoma cells may be an important indicator of occurrence of delayed relapse